Ethnoarchaeology of the Kel Tadrart Tuareg: Pastoralism and Resilience in Central Sahara - Biagetti, Stefano (Springer, 2020)
This book focuses on the issues of resilience and variability of desert pastoralists, explicitly challenging a set of traditional topics of the discourse around pastoralism in arid lands of the Old World. Based on a field research carried out on the Kel Tadrart Tuareg in Libya, various facets of a surprisingly successful adaptation to an extremely arid environment are investigated. By means of an ethnoarchaeological approach, explored are the Kel Tadrart interactions with natural resources, the settlement patterns, the campsite structures, and the formation of the pastoral archaeological landscape, focusing on variability and its causes. The resilience of the Kel Tadrart is the key to understand the reasons of their choice to stay and live in the almost rainless Acacus Mountains, in spite of strong pressure to sedentarize in the neighboring oases,...